ANALISIS IMPLEMENTASI PP NO.35 TAHUN 2021 TENTANG PERJANJIAN KERJA WAKTU TERTENTU, ALIH DAYA, WAKTU KERJA DAN WAKTU ISTIRAHAT, DAN PEMUTUSAN HUBUNGN KERJA DALAM PERSPEKTIF AGILE GOVERNANCE (STUDI DINAS KETENAGAKERJAAN KABUPATEN PASURUAN) - Febriyanti, Emilia; Aminullah, Aminullah (STKIP Pesisir Selatan, 2025)
The central government initiated has issued government regulation Number 35 of 2021 concerning Fixed-Term Employment Agreements (PKWT), Outsourcing, Working Hours and Rest Periods, as well as Termination of Employment. The aim of this regulation is to provide legal certainty for workers and employers regarding employment contracts. The implementation of this regulation still faces challenges and has not been optimally carried out, especially for small and medium enterprises. This research aims to understand and analyze the implementation of the recording of PKWT (Fixed Term Employment Agreements) in the perspective of Agile Governance at the Office of Manpower of Pasuruan Regency. The research method used in this study is a qualitative method that is descriptive in nature. Data collection techniques include observation, interviews, and documentation. The results of this study indicate that the implementation of Government Regulation No. 35 of 2021 regarding Fixed-Term Employment Agreements (PKWT), Outsourcing, Working Time and Rest Time, as well as Termination of Employment has not been maximally carried out. There are still companies that have not registered PKWT. The limited number of employees in handling various obligations both during consultative guidance and in administrative processes such as PKWT registration, along with the lack of resources in the guidance of PKWT registration, are factors that hinder progress.